Ethics at the workplace: collaborative teaching between APB UiTM NS and APB UiTM Melaka / Sheela Paramasivam ... [et al.] - Paramasivam, Sheela; Kasawi @ Krisnan, Alice Shanthi; Ibrahim, Raihan; Omar, Nur Hidayatul Shima; Kumar, KV Krishna (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Workplace ethics are crucial in any organisation to ensure its smooth operations and to help the organisation maintain specific standards of accountability, responsibility, and professionalism among leaders, employers, employees, stakeholders, customers, and the general public (Shafie et al., 2016). In this article, we outline what ethics in the workplace are, why they are important to establish, and what specific benefits organisations and stakeholders may enjoy from initiating an ethical code of conduct.